2009
DOI: 10.1111/j.1748-0159.2009.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole grain snack intake in an after‐school snack program: a pilot study

Abstract: US children consume about one‐third of the recommended level of whole grain. This study compared the difference in consumption between snacks made with either refined flour (Goldfish 0 g/serving), low (Graham crackers 5 g/serving, Goldfish 8 g/serving) or 100% whole grain flour level (Graham crackers 26 g/serving) among 117 children (kindergarten–sixth grade) participating in after‐school snack programs. The study included plate waste collection and group interviews conducted in four elementary schools in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…There are some wholegrain products available for use in school food service operations; however, the higher cost of wholegrain foods is an issue (4) , as is the acceptability by students (18) . A few studies suggest that inclusion of wholegrain foods in school lunches may be well received by children, but acceptance of 100 % wholegrain foods is lower than acceptance of 50 % wholegrain products (19,20) . In a previous focus group study identifying ways to promote new foods in the cafeteria, children reported that 'new foods would be accepted if they looked and tasted good and were familiar' and 'could be promoted through sampling, peer influence and providing incentives' (18) .…”
Section: Discussionmentioning
confidence: 99%
“…There are some wholegrain products available for use in school food service operations; however, the higher cost of wholegrain foods is an issue (4) , as is the acceptability by students (18) . A few studies suggest that inclusion of wholegrain foods in school lunches may be well received by children, but acceptance of 100 % wholegrain foods is lower than acceptance of 50 % wholegrain products (19,20) . In a previous focus group study identifying ways to promote new foods in the cafeteria, children reported that 'new foods would be accepted if they looked and tasted good and were familiar' and 'could be promoted through sampling, peer influence and providing incentives' (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the factors that may influence WG consumption (barriers and facilitators) was collected from studies addressing the consumer’s perception of products made with WG. The literature search allowed us to identify 13 studies in children [ 16 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], five in adolescents [ 33 , 43 , 44 , 45 , 46 ], and 30 studies in adults; more precisely for adults: 10 in young adults [ 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], 10 in middle-aged adults [ 16 , 31 , 37 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], four in older adults [ 17 , 62 , 63 , 64 ], two in young and middle-aged adults grouped together [ 65 , 66 ], and five that did not separate age groups and considered all adults together [ 15 , 67 , 68 , 69 , 70 ]. The data that were...…”
Section: Main Barriers To and Facilitators Of Whole Grain Consumptmentioning
confidence: 99%
“…The fruit and vegetable plate consisted of orange slices and cucumber slices. Tortilla chips were chosen as the alternate snack option based on their popularity in our target population and their high national incidence of consumption by children ages six to eleven (Sadeghi & Marquart, 2009). Unlike the previously referenced study, the current pilot method observed actual amount of snacks consumed as well the amount taken.…”
Section: Snack Preferencementioning
confidence: 99%